2020
DOI: 10.1101/2020.08.06.20169763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CoMix: comparing mixing patterns in the Belgian population during and after lockdown

Abstract: Background: The COVID-19 pandemic has shown how a newly emergent communicable disease can lay considerable burden on public health. To avoid system collapse, governments have resorted to several social distancing measures. In Belgium, this included a lockdown and a following period of phased re-opening. Methods: A representative sample of Belgian adults was asked about their contact behaviour from mid-April to mid-July, during different stages of the intervention measures in Belgium. Use of personal protection… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 27 publications
3
81
1
Order By: Relevance
“…As of Nov 30, total estimated attack rates are 20.7%(95%CI : 17.3%−24.1%) in Rhode Island and 12.5% (95% CI : 11.5% − 13.5%) in Massachusetts [ 21 ]. We upgraded the model parameterization by using age-contact matrices measured in Belgium (CoMix) which are representative of lockdown and post-lockdown mixing patterns in western countries [ 22 ]. The eight age-bands in the CoMix data [ 22 ] were transformed into our nine age-bands using the socialmixr R package [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As of Nov 30, total estimated attack rates are 20.7%(95%CI : 17.3%−24.1%) in Rhode Island and 12.5% (95% CI : 11.5% − 13.5%) in Massachusetts [ 21 ]. We upgraded the model parameterization by using age-contact matrices measured in Belgium (CoMix) which are representative of lockdown and post-lockdown mixing patterns in western countries [ 22 ]. The eight age-bands in the CoMix data [ 22 ] were transformed into our nine age-bands using the socialmixr R package [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…We upgraded the model parameterization by using age-contact matrices measured in Belgium (CoMix) which are representative of lockdown and post-lockdown mixing patterns in western countries [ 22 ]. The eight age-bands in the CoMix data [ 22 ] were transformed into our nine age-bands using the socialmixr R package [ 23 ]. Using median values from posteriors from the new model fit, the new model’s Nov 30 attack rates are 16.8% for RI and 16.5% for MA.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, we found that adherence was strongly correlated with individuals' symptoms compatible with COVID-19, as well as their age. Whether better adherence by younger age groups was biased by their lower and decreasing response rate and that therefore mainly those that are health-conscious participated in later waves, or the fact that people in older age groups have fewer contacts [8,9] and might not have defined their lack of contacts as 'quarantine/isolation', or whether this is a real effect, is yet unknown. Our findings on age differences were similar to observations made in Italy [10].…”
Section: A Covid-19-compatible Symptoms B Age Groups In Yearsmentioning
confidence: 99%
“…Thus, we used nine independent mixing rates for the nine age-classes in our model (and assumed that contact between two age groups is proportional to their two mixing rates); the data are unlikely to have enough resolution to infer 81 independent mixing parameters. As confidence grows in the survey methods used to collect post-pandemic age-contact data[37][38][39][40][41] these matrices should be included into modeling efforts like ours.Infectious disease epidemiology has been neglected in the United States for more than half a century because of our status as a developed country, with a secure food supply, a sanitary water system, few persistent disease vectors, high public hygiene standards, and ample supply of therapeutics and vaccines. We were not prepared in 1981 when the HIV epidemic was uncovered, and with no leadership from the federal government in 2020, we are underprepared at the state level for the SARS-CoV-2 epidemic as few individuals remain with knowledge from the early struggle against HIV.…”
mentioning
confidence: 99%